(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
As the European economy became monetized over the course of the later Middle Ages, object values began to appear in an extensive array of sources, typically in the form of estimates or value appraisals. Using records from the city of Marseille as a case study, this contribution considers a widespread practice that involved bundling or grouping a set of two or more objects and supplying a single value estimate to that bundle. Some value bundles consisted of sets of identical object types. In other cases, objects that were dissimilar to one another were combined in value bundles. In some cases involving the bundling of identical object types, the resulting values arose from unit-price thinking, that is, estimating the value of the object type and multiplying by the number of objects. Close reading of some representative sources, however, indicates that some values were applied to whole bundles, a situation that is especially evidence in cases where dissimilar objects were bundled. This contribution argues that variations in habits of value estimation provide important clues for understanding patterns of mathematical cognition in medieval European societies.